FRIENDSHIP: THE MYSTICISM OF AELRED OF RIEVAULX: Friendship - Henn, Katherine (Journal of Dharma, 1979)
To live is to love and to love is to suffer, the only other alternative is not to live," was the rather stoic response of Dr. Viktor Frankal when asked how he could have endured the deathcamp deaths of his friends and relatives and still continue to love. Why one should risk the potential pain involvement brings is a contemporary question, asked today not only illl the face of physical death but in the many deaths of relationships so prevalent around us.